Access to and challenges in water, sanitation, and hygiene in healthcare facilities during the early phase of the COVID-19 pandemic in Ethiopia: A mixed-methods evaluation. - Gete Berihun; Metadel Adane; Zebader Walle; Masresha Abebe; Yeshiwork Alemnew; Tarikuwa Natnael; Atsedemariam Andualem; Sewunet Ademe; Belachew Tegegne; Daniel Teshome; Leykun Berhanu (PLoS ONE, 2022)
Background Inadequate water, sanitation, and hygiene (WASH) in healthcare facilities (HCFs) have an impact on the transmission of infectious diseases, including COVID-19 pandemic. But, there is limited data on the status of WASH facilities in the healthcare settings of Ethiopia. Therefore, this study aimed to assess WASH facilities and related challenges in the HCFs of Northeastern Ethiopia during the early phase of COVID-19 pandemic. Methods An institution-based cross-sectional study was conducted from July to August 2020. About 70 HCFs were selected using a simple random sampling technique. We used a mixed approach of qualitative and quantitative study. The quantitative data were collected by an interviewer-administered structured questionnaire and observational checklist, whereas the qualitative data were collected using a key-informant interview from the head of HCFs, janitors, and WASH coordinator of the HCFs. The quantitative data were entered in EpiData version 4.6 and exported to Statistical Package for Social Sciences (SPSS) version 25.0 for data cleaning and analysis. The quantitative data on access to WASH facilities was reported using WHO ladder guidelines, which include no access, limited access, and basic access, whereas the qualitative data on challenges to WASH facilities were triangulated with the quantitative result. Results From the survey of 70 HCFs, three-fourths 53 (75.7%) were clinics, 12 (17.2%) were health centers, and 5 (7.1%) were hospitals. Most (88.6%) of the HCFs had basic access to water supply. The absence of a specific budget for WASH facilities, non-functional water pipes, the absence of water-quality monitoring systems, and frequent water interruptions were the major problems with water supply, which occurred primarily in clinics and health centers. Due to the absence of separate latrine designated for disabled people, none of the HCFs possessed basic sanitary facilities. Half (51.5%) of the HCFs had limited access to sanitation facilities. The major problems were the absence of separate latrines for healthcare workers and clients, as well as female and male staffs, an unbalanced number of functional latrines for the number of clients, non-functional latrines, poor cleanliness and misuse of the latrine. Less than a quarter of the HCFs 15 (21.4%) had basic access to handwashing facilities, while half 35 (50%) of the HCFs did not. The lack of functional handwashing facilities at expected sites and misuse of the facilities around the latrine, including theft of supplies by visitors, were the two most serious problems with hygiene facilities. Conclusion Despite the fact that the majority of HCFs had basic access to water, there were problems in their sanitation and handwashing facilities. The lack of physical infrastructure, poor quality of facilities, lack of separate budget to maintain WASH facilities, and inappropriate utilization of WASH facilities were the main problems in HCFs. Further investigation should be done to assess the enabling factors and constraints for the provision, use, and maintenance of WASH infrastructure at HCFs.